Laminate and packaging bag
Patent Information
- Application Number
- JP2023193275
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2039-06-14
AI Technical Summary
【0017】 本発明によれば、積層体の酸素バリア性及び水蒸気バリア性を維持しつつ、ヒートシールによる積層体の変形を抑制し、並びにリサイクル性に優れる積層体を提供することができる。
Smart Images

Figure 0007632568000009 
Figure 0007632568000010 
Figure 0007632568000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a packaging bag including the laminate. [Background technology]
[0002] Conventionally, resin films made of resin materials have been used as a constituent material of packaging bags. Since packaging bags are required to have various functions such as oxygen barrier properties and water vapor barrier properties depending on the contents to be filled, laminates made of multiple resin films are widely used. For example, a resin film made of a thermoplastic resin such as polypropylene or polyethylene alone cannot ensure sufficient strength for a packaging bag, so a resin film made of a polyester such as polyethylene terephthalate is laminated. In addition, for the purpose of improving the oxygen barrier property and water vapor barrier property, a resin film made of polyamide or a metal foil is laminated, or a vapor deposition film is formed on a resin film (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-202519 A Summary of the Invention [Problem to be solved by the invention]
[0004] Some packaging bags are provided with a zipper tape on the inside of the packaging bag (hereinafter, also referred to as a zippered packaging bag). When producing such a zippered packaging bag, the laminate and the zipper tape are heated to heat seal the laminate, and this heat sealing is performed by applying heat to the surface of the laminate opposite to the side where the zipper tape is heat sealed.
[0005] Generally, heat sealing between a laminate and a zipper tape requires longer heating than heat sealing between laminates. The above-mentioned laminate with improved strength and barrier properties is characterized by having a large number of layers and a large thickness, since it includes a resin film made of polyester or polyamide, a metal foil, etc. However, when such a laminate is used to heat seal a zipper tape, heating at a higher temperature than usual for a long period of time is required, and the laminate, particularly the layer on the heated side, may melt and deform its surface, resulting in a loss of appearance.
[0006] In recent years, along with the growing demand for the creation of a recycling-oriented society, attempts have been made to recycle and reuse packaging bags. However, when multiple different resin films are bonded together, it is difficult to separate the resin films from each other, making them unsuitable for recycling, and there has been a demand for packaging bags that impose less of a burden on the environment.
[0007] In order to suppress deformation of the laminate due to the above-mentioned heat sealing and to improve its recyclability, the inventors attempted to produce a zippered packaging bag using a laminate with a small number of layers, which included a stretched polypropylene resin film, an adhesive layer made of a two-component curing urethane adhesive, an aluminum vapor deposition film, and an unstretched polypropylene resin film. However, it has been found that the zippered packaging bag is formed by a former or the like provided in the packaging machine when it is produced and filled with contents, and that the forming process imposes a large bending load on the packaging bag, resulting in a deterioration in the oxygen barrier property and water vapor barrier property of the zippered packaging bag. It has also been found that the heating applied when the laminate and the zipper tape are heat-sealed further reduces the oxygen barrier property and water vapor barrier property of the zippered packaging bag.
[0008] The present invention has been made in order to solve the above problems, and an object of the present invention is to provide a laminate which maintains the oxygen barrier property and water vapor barrier property of the laminate, while suppressing deformation of the laminate due to heat sealing, and which has excellent recyclability.
[0009] A further object of the present invention is to provide a packaging bag comprising the laminate and a zipper tape. [Means for solving the problem]
[0010] The present invention relates to a coating composition for a substrate, comprising a substrate, an adhesive layer, and a sealant layer, and further comprising a vapor-deposited film between the adhesive layer and the sealant layer, the adhesive layer being a cured product of a two-component curing adhesive containing a polyester polyol and an isocyanate compound, the polyester polyol being a polyester polyol having an isocyanuric ring, the vapor-deposited film having a thickness of 1 nm or more and 140 nm or less, The laminate is characterized in that the substrate is a stretched resin film, the substrate and the sealant layer contain the same resin material, and the same resin material is polypropylene.
[0011] In the laminate according to the present invention, the sealant layer may be an unstretched resin film.
[0012] In the laminate according to the present invention, the content of the same resin material may be 90% by mass or more.
[0013] In the laminate according to the present invention, the thickness of the laminate may be 10 μm or more and 130 μm or less.
[0014] In the laminate according to the present invention, the adhesive layer may have a thickness of 0.5 μm or more and 6 μm or less.
[0015] In the laminate according to the present invention, the vapor-deposited film may be an aluminum vapor-deposited film.
[0016] The present invention provides a packaging bag comprising the above-mentioned laminate and a zipper tape, the zipper tape being located on the sealant layer, the substrate, the sealant layer and the zipper tape comprising the same resin material, and the same resin material being polypropylene. Effect of the Invention
[0017] According to the present invention, it is possible to provide a laminate which maintains the oxygen barrier property and water vapor barrier property of the laminate, is inhibited from being deformed by heat sealing, and has excellent recyclability.
[0018] Furthermore, according to the present invention, a packaging bag including the laminate and a zipper tape can be provided. [Brief description of the drawings]
[0019] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Diagram 2] FIG. 1 is a front view showing an example of a packaging bag including the laminate of the present invention and a zipper tape. [Diagram 3] 3 is a cross-sectional view showing the packaging bag shown in FIG. 2 as viewed along the line AA. [Figure 4] FIG. 1 is a front perspective view showing an example of a packaging bag including the laminate of the present invention and a zipper tape. [Diagram 5] FIG. 2 is a rear perspective view showing an example of a packaging bag including the laminate of the present invention and a zipper tape. [Figure 6] FIG. 1 is a front view showing an example of a packaging bag including the laminate of the present invention and a zipper tape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] (Laminate) As shown in FIG. 1, a laminate 10 of the present invention comprises a substrate 11, an adhesive layer 12, and a sealant layer 13, and further comprises a vapor-deposited film 14 between the adhesive layer 12 and the sealant layer 13.
[0021] The substrate and the sealant layer of the laminate of the present invention contain the same resin material, which is polypropylene, thereby improving the recyclability of the packaging bag including the laminate. In the present invention, the terms "same resin material" and "same resin material" mean that the resin classification is the same.
[0022] In the laminate, the content of the same resin material is preferably 90% by mass or more, more preferably 92% by mass or more, and even more preferably 94% by mass or more, which can further improve the recyclability. The content of the same resin material in the laminate means the ratio of the same resin material to the sum of the contents of the resin materials in the layers constituting the laminate.
[0023] The laminate has an oxygen permeability of 0.05cc / m at 23℃ and 90% relative humidity. 2 / day / atm or more 2.0cc / m 2 / day / atm or less is preferable, and 0.05cc / m 2 / day / atm or more 1.0cc / m 2 It is preferable that it is / day / atm or less. In the present invention, the oxygen permeability is measured in accordance with JIS K 7126.
[0024] The laminate has a water vapor permeability of 0.01 g / m at 40°C and 90% relative humidity. 2 / day / atm or more 2.0g / m 2 / day / atm or less, and 0.01 g / m 2 / day / atm or more 1.0g / m 2 It is preferable that it is / day / atm or less. In the present invention, the oxygen permeability is measured in accordance with JIS K 7129.
[0025] The thickness of the laminate is preferably from 10 μm to 130 μm, and more preferably from 15 μm to 110 μm, which can further suppress deformation of the laminate due to heat sealing.
[0026] (base material) The substrate includes polypropylene. The polypropylene may be any of a homopolymer, a random copolymer, and a block copolymer. A polypropylene homopolymer is a polymer of only propylene, a polypropylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene (e.g., ethylene, butene-1, 4-methyl-1-pentene, etc.), and a polypropylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of the above-mentioned α-olefin other than propylene.
[0027] The substrate is a stretched resin film. This can provide sufficient strength and heat resistance for a packaging bag. The stretched resin film may be a uniaxially stretched resin film or a biaxially stretched resin film. In addition, the stretched resin film may be a stretched polypropylene resin film made of polypropylene.
[0028] The substrate may be a laminate of two or more of the above-mentioned resin films. The laminate of resin films can be produced by utilizing a dry lamination method, a wet lamination method, an extrusion method, or the like.
[0029] The base material may contain additives such as fillers, plasticizers, antistatic agents, ultraviolet absorbers, inorganic particles, organic particles, release agents, and dispersants, as long as the additives do not impair the characteristics of the present invention.
[0030] The substrate may have an image formed on its surface. It is preferable to form the image on the adhesive layer side of the substrate, since this can prevent the formed image from coming into contact with the outside air. The image to be formed is not particularly limited, and may represent characters, patterns, symbols, combinations thereof, and the like. The image can be formed using a conventionally known ink, but is preferably formed using an ink derived from biomass, which allows the laminate to be used to produce a packaging bag with less environmental impact. The method for forming the image is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing.
[0031] The substrate is preferably subjected to a surface treatment. This can improve the adhesion with the adjacent layers. The method of the surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, and chemical treatments such as oxidation treatment using chemicals.
[0032] The thickness of the substrate is preferably 5 μm or more and 50 μm or less, more preferably 10 μm or more and 40 μm or less. This makes it possible to further suppress deformation of the laminate due to heat sealing. In addition, it is possible to improve the mechanical strength and processability of the laminate.
[0033] (adhesive layer) The adhesive layer is a cured product of a two-component curing adhesive containing a polyester polyol and an isocyanate compound, and the polyester polyol is a polyester polyol obtained by polycondensation of an ortho-oriented polyvalent carboxylic acid or an anhydride thereof with a polyhydric alcohol, a polyester polyol having a glycerol skeleton, or a polyester polyol having an isocyanuric ring. When a laminate having a vapor-deposited film is applied to a packaging bag, a bending load is applied to the laminate by a molding machine or the like, and there is a risk of cracks or the like occurring in the vapor-deposited film. Since the adhesive layer is a cured product of the above-mentioned two-component curing adhesive, even if cracks occur in the vapor-deposited film, the oxygen barrier property and water vapor barrier property of the laminate can be maintained. In addition, this eliminates the need to use a resin film or metal foil made of polyester or polyamide, and a laminate can be made with a small number of layers and a thin thickness, and the thermal load due to heat sealing between the laminate and the zipper tape can be reduced. Therefore, deformation of the laminate due to heat sealing can be suppressed.
[0034] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule. The isocyanate compound has two or more isocyanate groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.
[0035] As a specific example of a two-component curing adhesive containing a polyester polyol and an isocyanate compound, the PASLIM series sold by DIC Corporation can be used.
[0036] The two-component curing adhesive may further contain a plate-like inorganic compound, a coupling agent, cyclodextrin and / or a derivative thereof, and the like.
[0037] As the polyester polyol having two or more hydroxyl groups in one molecule as a functional group, the following [First Example] to [Third Example] can be used. [Example 1] Polyester polyol obtained by polycondensation of ortho-oriented polycarboxylic acid or its anhydride with polyhydric alcohol [Example 2] Polyester polyol with glycerol structure [Example 3] Polyester polyol with isocyanuric ring Each polyester polyol will be described below.
[0038] The polyester polyol according to the first example is a polycondensate obtained by polycondensing a polycarboxylic acid component containing at least one type of orthophthalic acid and its anhydride, and a polyhydric alcohol component containing at least one type selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. In particular, polyester polyols in which the content of orthophthalic acid and its anhydride relative to the total polyvalent carboxylic acid components is 70 to 100 mass % are preferred.
[0039] The polyester polyol according to the first example essentially contains orthophthalic acid and its anhydride as the polycarboxylic acid component, but may be copolymerized with other polycarboxylic acid components as long as the effect of the present embodiment is not impaired. Specifically, the polybasic acids include succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid, and other aliphatic polybasic acids, unsaturated bond-containing polybasic acids, such as maleic anhydride, maleic acid, and fumaric acid, alicyclic polybasic acids, such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid, aromatic polybasic acids, such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids, and other polybasic acids, such as p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Among these, succinic acid, 1,3-cyclopentanedicarboxylic acid, and isophthalic acid are preferred. Two or more of the above other polyvalent carboxylic acids may be used.
[0040] As a polyester polyol according to a second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In general formula (1), R1, R2, and R3 each independently represent H (hydrogen atom) or a group represented by the following general formula (2). [ka]
[0041] In formula (2), n represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene groups, 1,2-naphthylene groups, 2,3-naphthylene groups, 2,3-anthraquinonediyl groups, and 2,3-anthracenediyl groups, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 represents a group represented by general formula (2).
[0042] In general formula (1), at least one of R1, R2, and R3 must be a group represented by general formula (2). In particular, it is preferable that all of R1, R2, and R3 are groups represented by general formula (2).
[0043] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (2), a compound in which any two of R1, R2, and R3 are groups represented by general formula (2), and a compound in which all of R1, R2, and R3 are groups represented by general formula (2).
[0044] X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group. When X is substituted with a substituent, it may be substituted with one or more substituents, and the substituent is bonded to any carbon atom on X that is different from the free group. Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0045] In the general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0046] The polyester resin compound having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol with an aromatic polycarboxylic acid or an anhydride thereof in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0047] Examples of aromatic polycarboxylic acids or anhydrides thereof in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring, such as a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.
[0048] Examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.
[0049] The polyester polyol according to the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In the general formula (3), R1, R2, and R3 each independently represent "-(CH2)n1-OH (wherein n1 represents an integer of 2 to 4)" or a structure represented by the general formula (4). [ka]
[0050] In the general formula (4), n2 represents an integer of 2 to 4, n3 represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 is a group represented by the general formula (4).
[0051] In the general formula (3), the alkylene group represented by -(CH2)n1- may be linear or branched. Among them, n1 is preferably 2 or 3, and most preferably 2.
[0052] In the general formula (4), n2 represents an integer of 2 to 4; n3 represents an integer of 1 to 5. X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group.
[0053] When X is substituted with a substituent, it may be substituted with one or more substituents, and the substituent is bonded to any carbon atom on X that is different from the free group. Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group. The substituent for X is preferably a hydroxyl group, a cyano group, a nitro group, an amino group, a phthalimido group, a carbamoyl group, an N-ethylcarbamoyl group, or a phenyl group, and most preferably a hydroxyl group, a phenoxy group, a cyano group, a nitro group, a phthalimido group, or a phenyl group.
[0054] In the general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0055] In general formula (3), at least one of R1, R2, and R3 is a group represented by general formula (4). Of these, it is preferable that all of R1, R2, and R3 are groups represented by general formula (4).
[0056] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (4), a compound in which any two of R1, R2, and R3 are groups represented by general formula (4), and a compound in which all of R1, R2, and R3 are groups represented by general formula (4).
[0057] The polyester polyol having an isocyanuric ring represented by the general formula (3) can be synthesized by reacting a triol having an isocyanuric ring, an aromatic polycarboxylic acid or an anhydride thereof in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0058] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.
[0059] Examples of aromatic polycarboxylic acids or anhydrides thereof in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride, etc. These compounds may have a substituent on any carbon atom of the aromatic ring.
[0060] Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0061] Furthermore, examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol. Among these, polyester polyol compounds having an isocyanuric ring, which use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid as a triol compound having an isocyanuric ring, orthophthalic anhydride as an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and ethylene glycol as a polyhydric alcohol, are particularly excellent in oxygen barrier properties and adhesion and are therefore preferred.
[0062] The isocyanuric ring is highly polar and trifunctional, and can increase the polarity of the entire system and increase the crosslink density. From this viewpoint, it is preferable that the adhesive resin contains 5% by mass or more of the isocyanuric ring based on the total solid content of the adhesive resin.
[0063] The oxidation resistance of the polyester polyol is preferably 20 mg KOH / g or more, and more preferably 50 mg KOH / g or more, which allows the oxygen barrier property and water vapor barrier property of the laminate to be better maintained.
[0064] The isocyanate compound has two or more isocyanate groups in the molecule. The isocyanate compound may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by subjecting a known isocyanate blocking agent to an addition reaction by a known, conventional appropriate method. Among these, from the viewpoints of adhesiveness and retort resistance, polyisocyanate compounds having three or more isocyanate groups are preferred, and from the viewpoints of oxygen barrier property and water vapor barrier property, aromatic compounds are preferred.
[0065] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, biurets, and allophanates obtained by reacting these isocyanate compounds with low-molecular-weight active hydrogen compounds or alkylene oxide adducts thereof, or high-molecular-weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include polymeric active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.
[0066] The two-component curing adhesive used to form the adhesive layer may contain a phosphoric acid-modified compound, which can better maintain the oxygen barrier property and water vapor barrier property of the laminate. The phosphoric acid-modified compound is, for example, a compound represented by the following general formula (5) or (6). [ka] In general formula (5), R1, R2, and R3 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4. [ka] In the formula, R4 and R5 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group; n is an integer of 1 to 4, x is an integer of 0 to 30, and y is an integer of 0 to 30, except for the case where both x and y are 0.
[0067] More specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.
[0068] The content of the phosphate-modified compound in the two-component curing adhesive is preferably 0.005% by mass to 10% by mass, more preferably 0.01% by mass to 1% by mass. By keeping the content of the phosphate-modified compound within the above numerical range, the oxygen barrier property and water vapor barrier property of the laminate can be better maintained.
[0069] The two-component curing adhesive used to form the adhesive layer preferably contains a plate-like inorganic compound, which makes it possible to better maintain the oxygen barrier property and water vapor barrier property of the laminate. Examples of the plate-like inorganic compounds include kaolinite-serpentine group clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, antigorite, chrysotile, etc.) and pyrophyllite-talc group (pyrophyllite, talc, kerolite, etc.).
[0070] The two-component curing adhesive used to form the adhesive layer may contain a coupling agent, which can better maintain the oxygen barrier property and water vapor barrier property of the laminate. Examples of the coupling agent include a silane-based coupling agent, a titanium-based coupling agent, or an aluminum-based coupling agent represented by the following general formula (7). These coupling agents may be used alone or in combination of two or more kinds. [ka]
[0071] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β Examples of the silane include (aminoethyl) γ-aminopropyl methyl dimethoxysilane, N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane, and 3-triethoxysilyl-N-(1,3-dimethyl-butylidene).
[0072] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl nor titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and dicumyl phenyl oxyacetate titanate.
[0073] Specific examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer.
[0074] The two-component curing adhesive used to form the adhesive layer preferably contains cyclodextrin and / or a derivative thereof, which can better maintain the oxygen barrier property and water vapor barrier property of the laminate. Specifically, for example, cyclodextrin, alkylated cyclodextrin, acetylated cyclodextrin, hydroxyalkylated cyclodextrin, and other cyclodextrins in which the hydrogen atoms of the hydroxyl groups of the glucose units of cyclodextrin are substituted with other functional groups can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives may be any of α-cyclodextrin consisting of six glucose units, β-cyclodextrin consisting of seven glucose units, and γ-cyclodextrin consisting of eight glucose units. These compounds may be used alone or in combination of two or more. Hereinafter, these cyclodextrins and / or their derivatives may be collectively referred to as dextrin compounds.
[0075] From the viewpoint of compatibility and dispersibility in the resin composition, it is preferable to use a cyclodextrin derivative as the cyclodextrin compound. From the viewpoint of the polarity of the various resins, the degree of substitution is preferably in the range of 0.1 to 14 per glucose atom, and more preferably in the range of 0.3 to 8 per glucose atom.
[0076] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.
[0077] Examples of acetylated cyclodextrin include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, monoacetyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.
[0078] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.
[0079] The thickness of the adhesive layer is preferably from 0.5 μm to 6 μm, more preferably from 0.8 μm to 5 μm, and even more preferably from 1 μm to 4.5 μm, which allows the oxygen barrier property and water vapor barrier property to be better maintained.
[0080] The adhesive layer can be formed by coating on a substrate or the like and drying using a conventional method such as direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fontaine method, and transfer roll coating.
[0081] (Sealant layer) The sealant layer contains polypropylene. The polypropylene may be the same as that used for the base material. The sealant layer may be formed of an unstretched resin film or by melt extrusion of polypropylene.
[0082] The sealant layer is preferably subjected to the above-mentioned surface treatment.
[0083] The sealant layer may contain the above-mentioned additives as long as the properties of the present invention are not impaired.
[0084] The thickness of the sealant layer is preferably 5 μm or more and 120 μm or less, more preferably 10 μm or more and 100 μm or less. This makes it possible to suppress deformation of the laminate due to heat sealing. In addition, it is possible to improve the mechanical strength and processability. Furthermore, it is possible to improve the processability and puncture resistance of the laminate while maintaining the heat sealability of the sealant layer.
[0085] (evaporated film) The laminate further includes a vapor-deposited film between the substrate and the adhesive layer, or between the adhesive layer and the sealant layer, which provides the laminate with oxygen barrier properties and water vapor barrier properties.
[0086] Examples of the vapor-deposited film include vapor-deposited films containing metals such as aluminum, and inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide. Among these, from the viewpoint of oxygen barrier property and water vapor barrier property, an aluminum vapor deposition film is preferable.
[0087] As a method for forming a vapor-deposited film, a conventionally known method can be used, and examples of the method include physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.
[0088] The thickness of the deposited film is preferably 1 nm or more and 140 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 5 nm or more and 40 nm or less. By keeping the thickness of the deposited film within the above numerical range, the occurrence of cracks and the like in the deposited film can be prevented. When the vapor-deposited film is an aluminum vapor-deposited film, the film thickness is preferably 1 nm or more and 100 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. When the vapor-deposited film is a silicon oxide or aluminum oxide vapor-deposited film, the film thickness is preferably 1 nm or more and 140 nm or less, more preferably 5 nm or more and 30 nm or less, and even more preferably 5 nm or more and 20 nm or less.
[0089] Also, for example, a composite film consisting of two or more layers of vapor-deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition. The degree of vacuum in the vapor deposition chamber is 10 -2 ~10 -8 After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The film transport speed is preferably about 10 to 800 m / min, particularly about 50 to 600 m / min.
[0090] (Gas barrier layer) The laminate may have a gas barrier layer between any layers, for example, between the adhesive layer and the vapor-deposited film, which can improve the oxygen barrier property and water vapor barrier property of the laminate.
[0091] In one embodiment, the gas barrier layer comprises at least one resin composition, such as a hydrolysate of a metal alkoxide or a hydrolyzed condensate of a metal alkoxide, obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, and the like.
[0092] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.
[0093] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.
[0094] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (mass %) Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).
[0095] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, known organoalkoxysilanes containing organic reactive groups can be used, and in particular, organoalkoxysilanes having epoxy groups are preferred. Examples of organoalkoxysilanes having epoxy groups include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0096] Two or more of the above silane coupling agents may be used, and the silane coupling agent is preferably used in an amount within the range of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the alkoxide.
[0097] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier property, water vapor barrier property, water resistance and weather resistance, it is preferred to use these in combination.
[0098] The content of the water-soluble polymer in the gas barrier layer is preferably 5 parts by mass to 500 parts by mass per 100 parts by mass of the metal alkoxide, which can further improve the oxygen barrier property, water vapor barrier property and strength of the gas barrier layer.
[0099] The thickness of the gas barrier layer is preferably from 0.01 μm to 100 μm, and more preferably from 0.1 μm to 50 μm, which can effectively prevent cracks from occurring in the gas barrier layer while further improving the oxygen barrier property and water vapor barrier property.
[0100] The gas barrier layer can be formed by applying a composition containing an upper layer material onto a substrate by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coating, applicator, or the like, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable. As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable, and examples thereof include N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferable. The sol-gel catalyst is preferably used in the range of 0.01 to 1.0 parts by mass, more preferably 0.03 to 0.3 parts by mass, per 100 parts by mass of the metal alkoxide, which allows the thickness of the gas barrier layer to be uniform and further improves the catalytic effect.
[0101] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for the hydrolysis of alkoxides, silane coupling agents, and the like. As the acid, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. are used. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less based on the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. This allows the thickness of the gas barrier layer to be formed to be uniform, and the catalytic effect to be further improved.
[0102] The composition preferably contains water in an amount of 0.1 to 100 moles, more preferably 0.8 to 2 moles, per mole of the total molar amount of the alkoxides, which can improve the oxygen barrier property and water vapor barrier property of the gas barrier layer and can rapidly carry out the hydrolysis reaction.
[0103] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.
[0104] An embodiment of a method for forming a gas barrier layer will be described below. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied onto the vapor-deposited film by the above-mentioned conventionally known method, and then dried. This drying causes the polycondensation reaction of the alkoxide and the water-soluble polymer (as well as the silane coupling agent, if the composition contains a silane coupling agent) to proceed further, forming a composite polymer layer. Finally, the composition is heated at a temperature of 20 to 250° C., preferably 50 to 220° C., for 1 second to 10 minutes to form a gas barrier layer.
[0105] (Method of manufacturing laminate) The method for producing the laminate according to the present invention is not particularly limited, and it can be produced by using a conventionally known method such as a melt extrusion lamination method, a dry lamination method, or a sand lamination method.
[0106] The laminate according to the present invention can be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesion, printing, metallizing (plating, etc.), machining, and surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.). In addition, the laminate according to the present invention can be subjected to lamination (dry lamination and extrusion lamination), bag making, and other post-treatment processes to manufacture molded products.
[0107] (packaging bag) The packaging bag of the present invention comprises the laminate and a zipper tape, and the zipper tape is located on the sealant layer. The substrate and zipper tape of the packaging bag contain the same resin material, which is polypropylene. This can improve recyclability. The polypropylene contained in the zipper tape can be the same as that of the substrate. An example of the packaging bag according to the present invention will be described with reference to the drawings.
[0108] Fig. 2 is a front view showing an example of the packaging bag of the present invention. The flat bag 20 shown in Fig. 2 comprises body material films (using the above laminate) 21, 21' and a zipper tape 23, and has a through hole 22 in the upper part of the flat bag 20. The zipper tape is a member provided to reseal the packaging bag after it has been opened.
[0109] 3 is a cross-sectional view of the packaging bag 20 shown in FIG. 2 as viewed along the line AA. As shown in FIG. 3, the zipper tape 23 includes a male tape 24 attached to the inner surface of the body material film 21 and a female tape 25 attached to the inner surface of the body material film 21' so as to face the male tape 24. The male tape 24 and the female tape 25 are configured to be able to fit together. In this case, the packaging bag 20 can be resealed after opening by fitting the male tape 24 and the female tape 25 together. In addition, the contents can be taken out again by releasing the fitting between the male tape 24 and the female tape 25. Although not shown, the male tape 24 may be attached to the body material film 21' and the female tape 25 may be attached to the body material film 21.
[0110] Next, a method for manufacturing the flat bag 20 will be described with reference to FIG. First, the body material films 21 and 21' are prepared and arranged so that the sealant layers of the body material films 21 and 21' face each other. Next, the zipper tape 23 is inserted between the body material films 21 and 21' toward the upper side, and each of the body material films 21 and 21' and the zipper tape 23 are heat-sealed. Next, the lower parts of the body material films 21 and 21' are heat-sealed. Using a point seal bar, the protrusions of the male tape 24 and the female tape 25 of the zipper tape 23 located at the heat-sealed parts on both sides of the body material films 21 and 21' are crushed. Next, using a side seal bar, the heat-sealed parts on both sides of the body material films 21 and 21' are heat-sealed. Next, the male tape 24 is removed from the female tape 25 of the zipper tape 23 to open it, and the contents are filled from the opening at the top. Next, the male tape 24 and the female tape 25 are fitted together again to close the opening, and the top parts of the body material films 21 and 21' are heat-sealed. Finally, the through holes 22 are formed to produce the flat bag 20. Here, the hatched areas in Fig. 2 represent the heat-sealed areas. Alternatively, the flat bag 20 may be produced by first heat-sealing the upper portions of the body material films 21, 21', filling the contents, and then heat-sealing the lower portions of the body material films 21, 21'.
[0111] Figures 4 and 5 are front and rear perspective views showing another example of the packaging bag of the present invention. The pillow bag 30 shown in Figures 4 and 5 includes a body material film (using the above laminate) 31 and a zipper tape 33, and has a through hole 32 in the upper part of the pillow bag 30. The zipper tape 33 may be the same as the zipper tape 23 described in Figures 2 and 3.
[0112] Next, a method for manufacturing the pillow bag 30 will be described with reference to FIGS. First, the body material film 31 is prepared, and the zipper tape 33 is heat-sealed to the upper center on the sealant layer of the body material film 31. Next, the left and right ends of the body material film 31 are folded toward the center so that the zipper tape 33 is located inside, and the sealant layers are heat-sealed so as to join together. Next, the inner surface of the joining part side of the tubular body material film 31 and the zipper tape 33 are heat-sealed. Next, the lower part of the body material film 31 is heat-sealed. Next, the male tape of the zipper tape 33 is removed from the female tape to open it, and the contents are filled from the upper opening. Next, the male tape and the female tape are fitted together again to close the opening, and the upper part of the body material film 31 is heat-sealed. Finally, a through hole 32 is formed to manufacture a pillow bag 30. Here, the hatched parts in Figures 4 and 5 represent the heat-sealed parts. Alternatively, the pillow bag 30 may be produced by first heat-sealing the upper part of the body material film 31, filling the bag with the contents, and then heat-sealing the lower part of the body material film 31.
[0113] Fig. 6 is a front view showing another example of the packaging bag of the present invention. The stand pouch 40 shown in Fig. 6 comprises body material films (using the above laminate) 41, 41', a base material film (which may be the same as or different from the body material film) 44, and a zipper tape 43, and has a through hole 32 in the upper part of the stand pouch 40. The zipper tape 43 may be the same as the zipper tape 23 described in Figs. 2 and 3.
[0114] Next, a method for producing the stand pouch 40 will be described with reference to FIG. First, the body material films 41 and 41' are prepared, and the body material films 41 and 41' are arranged so that their sealant layers face each other. Next, the bottom material film 44 is folded inward and inserted between the lower parts of the body material films 41 and 41' to form a gusset portion, and the lower part of the boat bottom shape including the peripheral part is heat sealed. Next, the bottom material film 42 is folded inward and inserted between the lower parts of the body material films 41 and 41' to form a gusset portion, and the body material films 41 and 41' and the bottom material film 42 are heat sealed using a boat bottom-shaped heat seal hot plate. Using a point seal bar, the protrusions of the male tape and female tape of the zipper tape 43 located in the heat seal portion on both sides of the body material films 41 and 41' are crushed. Next, the heat seal portion on both sides of the body material films 41 and 41' is heat sealed using a side seal bar. Next, the male tape is removed from the female tape of the zipper tape 43 to open it, and the contents are filled from the upper opening. Next, the male tape and female tape are fitted together again to close the opening, and the upper parts of the body material films 41, 41' are heat sealed. Finally, a through hole 42 is formed to produce the stand pouch 40. Here, the shaded areas in Fig. 6 represent the heat sealed areas. Alternatively, the stand pouch 40 may be produced by first heat-sealing the upper portion of the body material film 41, filling the pouch with the contents, and then heat-sealing the lower portion of the body material film 31 and the base material film 44 together.
[0115] The contents filled in the packaging bag are not particularly limited, and the contents may be liquid, powder, or gel, in addition to solids. The contents may be food or non-food.
[0116] (Other Aspects) Another aspect of the present invention is a coating composition comprising a substrate, an adhesive layer, and a sealant layer, and further comprising a vapor deposition film between the adhesive layer and the sealant layer, the adhesive layer being a cured product of a two-component curing adhesive containing a polyester polyol and an isocyanate compound, the polyester polyol being a polyester polyol obtained by polycondensing an ortho-oriented polyvalent carboxylic acid or an anhydride thereof with a polyhydric alcohol, a polyester polyol having a glycerol skeleton, or a polyester polyol having an isocyanuric ring, The laminate is characterized in that the substrate is a stretched resin film, the substrate and the sealant layer contain the same resin material, and the same resin material is polypropylene. In the laminate according to another aspect of the present invention, the sealant layer may be an unstretched resin film. In the laminate according to another aspect of the present invention, the content of the same resin material may be 90% by mass or more. In the laminate according to another aspect of the present invention, the thickness of the laminate may be 10 μm or more and 130 μm or less. In the laminate according to another aspect of the present invention, the adhesive layer may have a thickness of 0.5 μm or more and 6 μm or less. In the laminate according to another aspect of the present invention, the vapor-deposited film may have a thickness of 1 nm or more and 140 nm or less. In the laminate according to another aspect of the present invention, the vapor-deposited film may be an aluminum vapor-deposited film. Another aspect of the present invention is a packaging bag comprising the above-mentioned laminate and a zipper tape, the zipper tape being located on the sealant layer, the substrate, the sealant layer and the zipper tape comprising the same resin material, and the same resin material being polypropylene. EXAMPLES
[0117] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0118] [Example 1] A biaxially oriented polypropylene resin film having a thickness of 30 μm was prepared as a substrate, and a printing layer was formed on the biaxially oriented polypropylene resin film by gravure printing. The thickness of the printing layer was 1 μm.
[0119] Next, an unstretched polypropylene resin film (manufactured by Toray Processing Film Co., Ltd., product name: VM-CPP 2703, thickness: 30 μm) with an aluminum vapor deposition film of 50 nm thickness on one side was prepared, and the printed surface of the biaxially stretched polypropylene resin film and the vapor deposition surface of the unstretched polypropylene resin film were laminated via a two-component curing adhesive containing polyester polyol and an isocyanate compound (manufactured by DIC Corporation, product name: PASLIM VM NSRD011 / NSRD006). The thickness of the adhesive layer formed by the two-component curing adhesive was 2.5 μm.
[0120] The thickness of the laminate thus obtained is 63.5 μm and the weight is 57.5 g / m 2 The proportion of polypropylene in the laminate was 93.9% by mass.
[0121] Next, using the laminate obtained in this example and a zipper tape containing polypropylene (manufactured by Takiron C.I. Co., Ltd., product name: zipper tape MX-13F, MX general-purpose grade), a flat bag 20 as shown in Fig. 2 was produced (processing conditions: sealing temperature 175°C, sealing time 0.30 seconds). The body material film (laminate) was not deformed by heat sealing.
[0122] [Example 2] A laminate was produced in the same manner as in Example 1.
[0123] Next, using the laminate obtained in this example and a zipper tape containing polypropylene (manufactured by Takiron C.I. Co., Ltd., product name: zipper tape MX-13FS, MX soft grade), a flat bag 20 as shown in Fig. 2 was produced (processing conditions: sealing temperature 175°C, sealing time 0.30 seconds). The body material film (laminate) was not deformed by heat sealing.
[0124] [Comparative Example 1] A polyethylene terephthalate (PET) resin film having a thickness of 12 μm was prepared as a substrate, and a print layer was formed on the PET resin film by gravure printing. The print layer had a thickness of 1 μm.
[0125] Next, an aluminum foil having a thickness of 7 μm was prepared, and the printed layer of the PET resin film and the aluminum foil were laminated via a two-component curing adhesive (manufactured by Rock Paint Co., Ltd., product name: Adlock, main agent: RU-77T, curing agent: H-7). The thickness of the adhesive layer formed by the two-component curing adhesive was 3 μm.
[0126] Next, a polyethylene resin film having a thickness of 60 μm was prepared, and the aluminum foil and the polyethylene resin film were laminated via a two-component curing adhesive (manufactured by Rock Paint Co., Ltd., product name: Adlock, main agent: RU-77T, curing agent: H-7). The thickness of the adhesive layer formed by the two-component curing adhesive was 3 μm.
[0127] The thickness of the laminate thus obtained was 86 μm.
[0128] Next, using the laminate obtained in this comparative example and a zipper tape containing polypropylene (manufactured by Takiron C.I. Co., Ltd., product name: zipper tape MX-13F, MX soft grade), a flat bag 20 as shown in Fig. 2 was produced (processing conditions: sealing temperature 175°C, sealing time 0.45 seconds). The body material film (laminate) was not deformed by heat sealing.
[0129] [Comparative Example 2] A laminate was produced in the same manner as in Example 1, except that the two-component curing adhesive of Example 1 (manufactured by DIC Corporation, product name: PASLIM VM NSRD011 / NSRD006) was changed to the two-component curing adhesive of Comparative Example 1 (manufactured by Rock Paint Co., Ltd., product name: ADOLOCK, base agent: RU-77T, curing agent: H-7). The thickness of the adhesive layer formed by the adhesive was 2.5 μm.
[0130] Next, using the laminate obtained in this comparative example and a zipper tape containing polypropylene (manufactured by Takiron C.I. Co., Ltd., product name: zipper tape MX-13F, MX general-purpose grade), a flat bag 20 as shown in Fig. 2 was produced (processing conditions: sealing temperature 175°C, sealing time 0.30 seconds). The body material film (laminate) was not deformed by heat sealing.
[0131] [Comparative Example 3] A biaxially oriented polypropylene resin film having a thickness of 30 μm was prepared as a substrate, and a printing layer was formed on the biaxially oriented polypropylene resin film by gravure printing. The thickness of the printing layer was 1 μm.
[0132] Next, a PET resin film (thickness 12 μm) having an aluminum deposition film was prepared, and the printed layer of the biaxially stretched polypropylene resin film and the PET resin film were laminated via a two-component curing adhesive (manufactured by Rock Paint Co., Ltd., product name: Adlock, main agent: RU-77T, curing agent: H-7). The thickness of the adhesive layer formed by the two-component curing adhesive was 3 μm.
[0133] Next, a 30 μm thick unstretched polypropylene resin film was prepared, and the PET resin film of the biaxially stretched polypropylene resin film and the unstretched polypropylene resin film were laminated via a two-component curing adhesive (manufactured by Rock Paint Co., Ltd., product name: Adlock, main agent: RU-77T, curing agent: H-7). The thickness of the adhesive layer formed by the two-component curing adhesive was 3 μm.
[0134] The thickness of the laminate thus obtained was 79 μm.
[0135] Next, a flat bag 20 as shown in Fig. 2 was produced using the laminate obtained in this comparative example and a zipper tape containing polypropylene (manufactured by Takiron C.I. Co., Ltd., product name: zipper tape MX-13F, MX soft grade) (processing conditions: sealing temperature 175°C, sealing time 0.45 seconds). The body material film (laminate) was deformed by heat sealing.
[0136] <<Oxygen Barrier Test>> The laminates obtained in the above Examples and Comparative Examples were cut to A4 size, and the oxygen permeability (cc / m) was measured using OXTRAN 2 / 20 manufactured by MOCON, USA, at 23°C and a relative humidity of 90%. 2 / day / atm) were measured. The measurement results are summarized in Table 1.
[0137] <<Water vapor barrier test>> The laminates obtained in Example 1 and Comparative Examples 1 to 3 were cut into A4 size pieces, and the water vapor permeability (g / m) was measured at 40°C and 90% relative humidity using a PERMATRAN 3 / 31 manufactured by MOCON, USA. 2 / day / atm) were measured. The measurement results are summarized in Table 1.
[0138] <<Flexibility load test>> The laminates obtained in the above Examples and Comparative Examples were subjected to a bending load (stroke: 155 mm, bending motion: 440°) five times in accordance with ASTM F 392 using a Gelbo Flex Tester (Tester Sangyo Co., Ltd., product name: BE1006BE). After applying the flexural load, the oxygen permeability and water vapor permeability were measured in the same manner as in the oxygen barrier property test and water vapor barrier property test. The measurement results are shown in Table 1.
[0139] [Table 1] [Explanation of symbols]
[0140] 10: Laminate 11: Base material 12: Adhesive layer 13: Sealant layer 14: Evaporation film 20: Flat bag 21,21': Body material film 22:Through hole 23: Zipper tape 24: Male tape 25: Female tape 30: Pillow bag 31: Body material film 32:Through hole 33: Zipper tape 40: Stand pouch 41,41': Body film 42:Through hole 43: Zipper tape 44: Base film
Claims
1. A substrate, an adhesive layer, and a sealant layer are provided, Further comprising a deposition film between the adhesive layer and the sealant layer; the adhesive layer is a cured product of a two-component curing adhesive containing a polyester polyol and an isocyanate compound, the polyester polyol is a polyester polyol having an isocyanuric ring, The substrate is a stretched resin film, The thickness of the vapor-deposited film is 1 nm or more and 140 nm or less, the substrate and the sealant layer contain the same resin material; The same resin material is polypropylene, The content of the same resin material is 90% by mass or more, A laminate having an oxygen transmission rate of 1.0 cc / m 2 / day / atm or less in an environment at 23° C. and a relative humidity of 90%.
2. The laminate according to claim 1 , wherein the sealant layer is an unstretched resin film.
3. The laminate according to claim 1 or 2, wherein the thickness of the laminate is from 10 μm to 130 μm.
4. The laminate according to any one of claims 1 to 3, wherein the adhesive layer has a thickness of 0.5 µm or more and 6 µm or less.
5. The laminate according to any one of claims 1 to 4, wherein the vapor-deposited film is an aluminum vapor-deposited film.
6. The laminate according to any one of claims 1 to 5, a zipper tape; the zipper tape is positioned on the sealant layer; the substrate, the sealant layer and the zipper tape contain the same resin material; A packaging bag, wherein the same resin material is polypropylene.
Citation Information
Patent Citations
Packaging bag with zipper tape
JP2006176196A
Gas barrier film, packaging material, package
JP2009202519A
Gas barrier multilayer film having layer including aluminum vapor deposition layer or aluminum foil
JP2013147014A
Multilayer film and standing pouch
JP2013237154A
Bag body with zipper tape and method of storing article
JP2018061903A